Targeting acid ceramidase ameliorates fibrosis in mouse models of non-alcoholic steatohepatitis - Yu, Amy; Cable, Carson; Sharma, Sachin; Shihan, Mahbubul H.; Mattis, Aras N.; Mileva, Izolda; Hannun, Yusuf A.; Duwaerts, Caroline C.; Chen, Jennifer Y. (Frontiers in Medicine, 2022)
Nonalcoholic fatty liver disease (NAFLD) is a common cause of liver disease worldwide, and is characterized by the accumulation of fat in the liver. Nonalcoholic steatohepatitis (NASH), an advanced form of NAFLD, is a leading cause of liver transplantation. Fibrosis is the histologic feature most associated with liver-related morbidity and mortality in patients with NASH, and treatment options remain limited. In previous studies, we discovered that acid ceramidase (aCDase) is a potent antifibrotic target using human hepatic stellate cells (HSCs) and models of hepatic fibrogenesis. Using two dietary mouse models, we demonstrate that depletion of aCDase in HSC reduces fibrosis without worsening metabolic features of NASH, including steatosis, inflammation, and insulin resistance. Consistently, pharmacologic inhibition of aCDase ameliorates fibrosis but does not alter metabolic parameters. The findings suggest that targeting aCDase is a viable therapeutic option to reduce fibrosis in patients with NASH.